Tear neuropeptides are associated with clinical symptoms and signs of dry eye patients - Yirou Zhang; Hong Zhang; Xingyu Zhu; Han Ye; Kan Yang; Xujiao Zhou; Jiaxu Hong (Annals of Medicine)
Purpose To evaluate levels of 3 tear-soluble neuropeptides in dry eye patients and to identify the correlations with clinical signs and symptoms.Methods A total of 16 dry eye patients and 12 healthy volunteers were enrolled. Dry eye disease (DED) diagnosis was based on the 2017 Report of the Tear Film & Ocular Surface Society International Dry Eye Workshop (TFOS DEWS II). First time of noninvasive breakup time (NIBUT-1st), mean time of noninvasive breakup time (NIBUT-avg), tear meniscus height (TMH), Schirmer test, corneal fluorescein staining (CFS) score and ocular surface disease index (OSDI) were recorded. Tear fluid samples were collected and enzyme-linked immunoassay (ELISA was performed to analyze levels of calcitonin gene-related peptide (CGRP), neuropeptide Y (NPY) and substance P (SP), as well as the association among the 3 neuropeptides and clinical findings.Results Compared to normal controls, levels of tear CGRP (p=.003) and SP (p=.002) were significantly decreased in dry eye patients yet not NPY concentrations. Levels of tear CGRP and SP showed an inverse correlation with CFS and OSDI, which positively correlated with NIBUT-1st, NIBUT-avg and Schirmer test values. Multiple linear regression analysis showed that Schirmer test values were related to tear CGRP concentration. Subgroup analysis showed lower tear CGRP concentration in DED patients with severe symptoms (OSDI ≥ 46).Conclusions Levels of tear CGRP and SP decreased in DED patients and showed meaningful correlations with clinical symptoms and signs, implying a potential relationship between tear neuropeptides and ocular neurosensory function.